Importance of the Supportive-educative System of Orem Model in the patient compliance - Reflexive study - Alexsandra Rodrigues Feijão; Marcos Venícios de Oliveira Lopes; Marli Teresinha Gimeniz Galvão (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2009)
The study aims to analyze critically the importance of the Supportive-Educative Systeml of Orem model to the therapy following, that is, compliance. The model of analysis we have chosen was proposed by Chinn and Kramer and it embraces processes for critical reflection of a theory, from which we used the criterion importance. It has twelve (12) questions as a guide. Among them, we have chosen three, which were related to the aspect of nursing practice, and they were adapted to the study objective. They are: 1. Does the theory have power to influence nursing actions in order to educate and stimulate therapy following? 2. How specific are the theory purposes? Do they provide a general structure for nursing action on compliance? Do they subsidize the presumption phenomena? 3. Will the application of this theory help in the solution of problems related to the compliance? Reflecting on these questions and on the aspects which are inherent in nursing care in relation to compliance, we considered the importance of the Supportive-Educative System to help the nurse in the encouragement and support for the therapy following by the patients. This system is based on dialogue, interaction, interdependence and co-responsibility between the subjects involved, what provides structural archetype for planning, behavior and evaluation of nursing assistance in the incentive and support for the therapy following.